Pengaruh Pendidikan Kesehatan Menggunakan Leaflet terhadap Sikap Ibu dalam Pemberian MP-ASI pada Bayi Usia < 6 Bulan - Kartini S; Harmawati Rustan; Hartati S (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The Complementary Food Supply Program (MPASI) was designed to replace breast milk supply for infants older than 6 months so that the two do not overlap. The aim of this study is to analyze the effect of health education through leaflets on mothers' attitudes towards providing MPASI to infants under 6 months of age. The research method used was a quasi-experimental one-group post-test design. Population and sample consisted of all mothers who had children younger than 6 months, i.e. a total of 30 people. The Wilcoxon test was used for data analysis. The results showed a p value of 0.000, indicating that health education through pamphlets influences mothers' attitudes towards providing MPASI to infants under 6 months of age. This study has important implications for health care providers. Design more effective health education programs tailored to the needs of mothers in the region.